ANALISIS DEFORMASI DAN GAYA-GAYA DALAM BALOK TRANSFER PADA METODE KONSTRUKSI BERTAHAP UNTUK BANGUNAN GEDUNG TINGGI - Aditung, Dipasanto; Tanijaya, Jonie; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2025)
The construction sequence analysis method is used to plan the order of construction and evaluate its effects on the structural performance of buildings. This study investigates the influence of transfer beams on deformation and internal forces in high-rise buildings by comparing the conventional method with the staged construction method. Structural modeling was carried out using ETABS software with load data and load combinations based on SNI 1727:2020 and response spectrum analysis based on SNI 1726:2019. The results show that the maximum deflection increased by 92% in buildings without transfer beams and by 169% in buildings with transfer beams. The maximum moment increased by 54% and 66%, respectively. The maximum normal force increased by 42% in both models, while the shear force increased by 50% in buildings without transfer beams and by 61% in buildings with transfer beams. Overall, buildings with transfer beams experience greater increases in deflection and internal forces compared to buildings without transfer beams.